Soluble polybenzimidazoles with intrinsic porosity: synthesis, structure, properties and processability - Kumar, Vikas; Chatterjee, Shyambo; Sharma, Pragati; Chakrabarty, Suman; Avadhani, Chilukuri V.; Sivaram, Swaminathan (56Journal of Polymer Science Part A-Polymer Chemistry, 2018)
We have explored two novel comonomers, namely, 4,16-dicarboxyl[2.2]paracyclophane and 5,5,6,6-tetraamino-3,3,3,3-tetramethyl-1,1-spirobi[indane], for the synthesis of co-polybenzimidazoles (co-PBIs) with intrinsic porosity. Both these monomers possess twisted structures that can lead to awkward macromolecular shapes that cannot pack efficiently. The consequences of introducing these two monomers on the structure and properties of PBIs are reported. The random copolymers synthesized are amorphous and possess glass transition temperatures (T(g)s) greater than 400 degrees C. T-g decreases with increasing comonomer content indicating an increase in fractional free volume. The copolymers have low surface area. TEM and BET measurements show evidence of mesopore formation. The copolymers show significant carbon dioxide adsorption. Single chain molecular dynamics simulation of 24-mer repeat units shows intramolecular void spaces arising as a result of distorted polymer chain with reduced conformational mobility. These studies define a new synthetic strategy for bottoms-up synthesis of PBIs with intrinsic porosity. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1046-1057

Lithium speciation in the LiPF6/PC electrolyte studied by two dimensional heteronuclear overhauser enhancement and pulse field gradient diffusometry NMR - Kumar, Vikas; Reddy, R. Ravikanth; Kumar, B. V. N. Phani; Avadhani, Chilukuri V.; Ganapathy, Subramanian; Chandrakumar, Narayanan; Sivaram, Swaminathan (Journal of Physical Chemistry C, 2019)
Electrolytic dissociation of lithium hexafluorophosphate (LiPF6) in the nonaqueous cyclic propylene carbonate (PC) has been investigated in the wide range of concentration (0.05-3.5 M) by Li-7 solution-state nuclear magnetic resonance (NMR) spectroscopy. Two-dimensional heteronuclear Overhauser enhancement spectroscopy NMR experiments have not only enabled the cation solvation and ion-pairing to be directly monitored but additionally evidence anion solvent interaction at higher concentrations (>1.2 M) of the PC electrolyte. Preliminary analysis of kinetic nOe data has been made to determine site-dependent cross-relaxation rates for the spatial interaction of the solvent with the Li+ cation and the PF6- anion. The concentration dependence of the Li-7 NMR self-diffusion coefficient (D-self), determined using very strong pulsed magnetic field gradients (similar to 1700 Gauss/cm), depicts two breaks to mark the solvation and ion-pairing events in a distinct manner. This in turn has aided the determination of solvent coordination number and average sizes of solvated and ion-paired clusters. Our results indicate that in the contact ion pair (CIP)-dominated electrolyte (>2 M), lithium-ion mobility across the solvated and ion-paired environments appears to be inhibited which makes the spectral distinction of solvated and ion-paired environments possible. The concentration dependence of the Li-7 NMR spectral and diffusometry data is in striking correspondence with that of bulk conductivity measurements and point to the detrimental effect of CIP aggregates in impeding the ionic conductivity at high salt concentrations. These results have significance in understanding the structure and dynamics of lithium-ion solvates that are ubiquitous in the working environment of a lithium-ion battery.